Conductivity comparison of calix[8]arene-MWCNTs through spin coating technique - Faridah Lisa Supian,; Lim, Darvina Choo Kheng; Amira Shakila Razali, (Penerbit Universiti Kebangsaan Malaysia, 2017)
In this study, we investigated the conductivity enhancement of calix[8]arene-multi-walled CNTs (MWCNTs) thin film. Two types of calix[8]arenes were used, which were 5,11,17,23,29,35,41,47-p-tert-butyl-49,50,51,52,53,54,55,56-oktakis[(carboxy)-pentoxy] -calix[8]arene (C[8]1) and 49,50,51,52,53,54,55,56 -octahydroxycalix[8]arene (C[8]2). The monolayer properties of these two types of calix[8]arene on water subphase were examined. Later, the thin films were fabricated by combining different ratios of each types of calix[8]arene with MWCNTs using spin coating deposition technique. Then, the developed thin films were characterized using surface potential meter and four point probe. Thin films of C[8]2 with hydroxyl groups at lower rims demonstrated higher surface potential and conductivity as compared to the thin films of C[8]1 with upper rims of tert-butyl groups and lower rims of carboxyl groups. These results indicated that the conductivity of calixarene thin films can be enhanced by MWCNTs through simple spin coating technique.